Flash Catalyst CS5 bible - Huddleston, Rob. (Indianapolis, IN : Wiley Pub., 2010)
"Create rich, Internet applications without writing any code. Imagine being able to build visually rich applications without writing code. That's exactly what Flash Catalyst enables you to do--and this step-by-step guide shows you how. You'll learn how to use all of Flash Catalyst's functionality to draw shapes, import images, add animations, incorporate multimedia, and more. Convert your Photoshop and Illustrator designs to Flash-based apps, improve your design and development, and create interactivity like never before with this computer guide. Create basic wireframes of applications using drawing tools. Take advantage of Flash Builder and the Flex framework. Build desktop applications using the Adobe Integrated Runtime. Integrate Flash movies, sound, and video into your site. Transform your design from illustrator into a completed project. Convert artwork to components and connect to live data."--Page 4 of cover.
Part I: Rich Internet Applications and the Flash Platform -- pt. II: Designing the Application -- pt. III: Creating the Application in Catalyst -- pt. IV: Exporting Projects into Flash Builder 4 -- pt. V: Build a Complete Project -- pt. IV: Appendixes.
Print version record.
English.
John Wiley and Sons
Keywords: Adobe Illustrator (Computer file); Flex (Computer file); Flash (Computer file); Fireworks (Computer file); ColdFusion; Adobe Illustrator (Computer file); Flex (Computer file); Flash (Computer file); Fireworks (Computer file); ColdFusion; Adobe Illustrator (Computer file); ColdFusion; Fireworks (Computer file); Flash (Computer file); Flex (Computer file); Computer graphics; Computer animation; User interfaces (Computer systems); Web sites -- Design; Infographie; Animation par ordinateur; Interfaces utilisateurs (Informatique); Sites Web -- Conception; computer graphics; computer animation; COMPUTERS -- Computer Graphics; Computer animation; User interfaces (Computer systems); Web sites -- Design; Computer animation; Computer graphics; User interfaces (Computer systems); Web sites -- Design